Joaquín Casalduero, Sentido y forma del "Quijote" (1605-1615). 2a. ed. Ínsula, Madrid, 1966; 405 pp.-3a. ed., ibid., 1970; 405 pp. - Kersten, Raquel (El Colegio de México, 1970)
Se reseñó el libro: Sentido y forma del "Quijote" (1605-1615).